Prediksi Jumlah Permintaan Koran Menggunakan Metode Jaringan Syaraf Tiruan Backpropagation - Nabilla Putri Sakinah; Imam Cholissodin; Agus Wahyu Widodo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
In the era of globalization, community needs for information is increasing by years. This can be seen from the behavior of the community in responding to everything, both global and national. The quantity of media provided convenience for the community to get information actually. Print media is one of media which has actuality and accuracy which can be trusted. One example of media is print media or newspaper. Newspaper is information tool and educational tool which until nowstill useful for every community. There are many forecasting methodthat have been used to predict which is proven in some forecasting and providing the good result, for example forecasting of water consumption, rainfall consumption, the exchange rate of dollar and forecasting electrical load. In accordance with the tests conducted using the data sales of Radar Madura in 2015, resulted the best iterations is 200, and the value of learning rate is 0.6, and the test of training data and test data yields the best value of training data is 100 and test data 10. With error rate 0.0162.